The Basic Empathy Scale: Validation of Empathy Measurement of Pesantren Students in Indonesia - Rizkiyanti, Charyna Ayu; Hermansyah, Eka; Wijayanti, Zaima Bunga (Universitas Islam Indonesia, 2025)
Over the past decade, the Basic Empathy Scale (BES) has become a standard tool for measuring empathy. Despite the reliability and cross-cultural applicability, challenges remain regarding the validity and generalizability. This study aimed to validate the BES using Rasch model to establish the reliability and validity of the instrument in measuring empathy. Participants in validation consisted of 200 students from Islamic Boarding Schools (Pesantren) in Java, Indonesia. This analysis was conducted using a quantitative method with Rasch model analysis by incorporating a Wright map, item fit analysis, a unidimensionality test, and Different Item Functioning (DIF). The results showed that the BES was reliable for measuring cognitive and affective empathy, confirming unidimensionality and item fit among participants. These findings implied that the BES was suitable for application among Islamic Boarding School students. DIF analysis further showed that some items might require revision to elicit more accurate results even though the instrument was considered valid and reliable.